PENGARUH SELEKSI DAN PEMBINAAN DOSEN TERHADAP KINERJA DOSEN PADA SEKOLAH TINGGI PARIWISATA TRISAKTI JAKARTA - Darsiah, Anis (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2018)
Selection is a fundamental thing to do to human resources, especially to High School Trisakti Tourism Jakarta. In addition to the selection required coaching lecturers. The purpose of this study is to know how big the influence of lecturer selection and coaching either separately (partially) or simultaneously (simultaneously) to the performance of the lecturer of Trisakti High School Trisakti Jakarta. To answer the purpose of the study was made with 5 kinds of answers from each of the 15 questionnaire research variables according to Likert scale. From the results of the answers will be obtained kusioner score for each independent variable and dependent variable. Then, the regression equation formula is determined after validity test, reliability test, and normality test on each questionnaire result and score both for dependent variable and score of independent variable. The results showed that the variables of selection and coaching lecturers either separately or together significantly influence the performance of the lecturers of Trisakti High School Trisakti Jakarta. with 99% accuracy. Percentage of influence of free variable selection on lecturer performance of Trisakti High School of Tourism Jakarta. is 66,2%, while for lecturer coaching is 59,6%. While simultaneously the influence of selection and guidance of lecturers on the performance of lecturers of High School Trisakti Jakarta Tourismis69.6%.